Potential benefits and toxicity of nanoselenium and nitric oxide in peppermint - Hossein NAZERIEH; Zahra ORAGHI ARDEBILI; Alireza IRANBAKHSH (Acta Agriculturae Slovenica)
Taking account of nano-compounds and biofortification, this research was conducted to evaluate peppermint (Mentha x piperita L.) responses to nano-selenium (nSe; 0, 2, and 20 mg l-1) and/or nitric oxide (NO; 0 and 8 mg l-1). Significant increases in leaf length, and area, and shoot fresh mass were enhanced by the low level of nSe and/or NO, contrasted with the high dose. The inhibitory effects of the high dose of nSe on the growth-related characteristics were significantly mitigated by NO. The adverse impact of nSe20 on chlorophyll concentration was alleviated by NO. The individual and combined treatments of nSe2 led to the significant inductions in the activities of nitrate reductase and peroxidase, whereas nSe20 inhibited. The proline contents in the nSe and/or NO-treated plants were higher than in the control. The nSe and/or NO provoked stimulation in activities of phenylalanine ammonia lyase enzyme. The foliar applications of nSe and/or NO triggered the accumulations of soluble phenols. Interestingly, the toxicity of nSe at the high dose led to the severe cell destruction in the cortex layer of the basal stem, which was partially alleviated by NO. The simultaneous applications of these supplements may consider as an alternative strategy for fortifying and improving plant protection, regarding sustainable agriculture.